2018
DOI: 10.1002/aenm.201803287
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Copper Phthalocyanines: A Strategy in Developing Dopant‐Free Hole‐Transporting Materials for Efficient and Ambient‐Stable Perovskite Solar Cells

Abstract: production cost, simple processability, and remarkably high power conversion efficiency (PCE). [1][2][3][4] A great deal of research effort has been dedicated to the development of PSCs, including perovskite compositional engineering, advanced deposition techniques for the fabrication of high-quality perovskite films, device architecture design, and charge-selective layer optimization, as well as stability improvement etc. [5][6][7][8][9] In just a few years, the PCE of PSCs has been dramatically increased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 65 publications
(81 reference statements)
3
91
0
Order By: Relevance
“…2.4 eV), and low onset potential. Meanwhile, porphyrins can be chosen as a mediator to maximize charge utilization as compared to previously reported photosensitizers, since they show relatively high hole mobility and it is possible to adjust their optical and electronic properties by modifying the peripheral and nonperipheral substituents and metal center …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…2.4 eV), and low onset potential. Meanwhile, porphyrins can be chosen as a mediator to maximize charge utilization as compared to previously reported photosensitizers, since they show relatively high hole mobility and it is possible to adjust their optical and electronic properties by modifying the peripheral and nonperipheral substituents and metal center …”
Section: Figurementioning
confidence: 99%
“…Meanwhile,p orphyrins can be chosen as am ediator to maximize charge utilization as compared to previously reported photosensitizers, [28] since they show relatively high hole mobility [29] and it is possible to adjust their optical and electronic properties by modifying the peripheral and nonperipheral substituents and metal center. [30] In this study,anovel interface charge modulation system was designed, and the resulting configuration (R-BV/CoPy/ FN-H, Figure 1a;h erein, reduced BiVO 4 ,5 ,10,15,20-tetrakis(4-carboxyphenyl)porphyrin-Co,a nd FeNi(OH) x are denoted as R-BV,C oPy,a nd FN-H, respectively) presented ah igh photocurrent of 4.75 mA cm À2 at 1.23 V( versus the reversible hydrogen electrode (RHE)) under AM 1.5 G illumination (100 mW cm À2 ). Intensity modulated photocurrent spectroscopy (IMPS) and I-t curves tests further revealed that CoPy (as the interface charge transfer mediator in the system) efficiently suppresses the interface recombination of accumulated holes with electrons,which is analogous to athe role of the volleyball setter in av olleyball match.…”
mentioning
confidence: 99%
“…After that, high PCEs of 16.91% and 18.92% were accomplished in PSCs by using the methoxydiphenylamine substituted carbazole as HTMs in 2016 and 2018, respectively, as reported by Nazeeruddin, Getautis and Snaith et al Most recently, Sellinger and Snaith et al reported PCEs over 18% and >1000 h operational stability by applying a lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)‐free carbazole‐based HTM, ET44, in PSCs . Although promising device performance in PSCs have been verified with carbazole‐based HTMs, the PCEs of related devices still cannot rival the efficiency rendered by the well‐known HTM‐Spiro‐OMeTAD (2,2′,7,7′‐tetrakis‐( N , N ‐di‐ p ‐methoxy‐phenyl‐amine)9,9′‐spirobifluorene) in PSCs . Particularly, the fundamental understanding of the impact of linking topology on the properties of carbazole‐based HTMs is lacking, and such knowledge is vital for future design concepts for even more efficient carbazole‐based HTMs for the application in high‐performance ssMSCs.…”
Section: Introductionmentioning
confidence: 73%
“…Metal phthalocyanines (MPcs) are highly thermal, chemical, and photostable p ‐type semiconductors, with intense absorption in the near‐infrared region, and are intensely used in thin‐film transistors and organic solar cells, which make them an interesting class of HTMs for PSCs . These low‐cost materials also offer relatively high hole mobility and high hydrophobicity . MPc's special properties can be adjusted by introducing various peripheral and nonperipheral substitutions with different electronic and spatial properties, as well as changing metal centers to control their structural and energetic features .…”
Section: Methodsmentioning
confidence: 99%
“…Sun and co‐workers introduced 4‐butylphenoxy and 4‐butoxyphenoxy groups as nonperipheral substituents to CuPc, and the isomer mixtures of CuPc‐Bu and CuPc‐OBu materials are prepared and used as dopant‐free HTMs in PSCs . They have reported PCEs of 14.3% and 17.6% for remarkably stable devices based on CuPc‐Bu and CuPc‐OBu HTMs, respectively.…”
Section: Methodsmentioning
confidence: 99%